Digital disbursements over crowdfunding platform for start-ups in India with blockchain technology: a conceptual framework. (13th December 2021) - Upadhyay, Chandra Kant; Pandiya, Bhartrihari; Tewari, Vijayshri
The purpose of this paper is to connect the concepts of crowdfunding with entrepreneurship and how blockchain technologies can be introduced for the safety of the business and speedy transactions. The source of raising funds usually for business start-ups has expanded with most businesses using crowdfunding platforms to raise funds as it is economical and straightforward in nature. A model has been framed which describes an approach by which a start-up can connect to crowdfunding for its initial finances. A systematic and comprehensive literature review was undertaken to study the research done till now. To understand the current scenario the trend and future of this concept, Google Trends was used putting keywords. The various stakeholders in the transaction like investors, entrepreneurs, customers, and crowdfunding platforms are interconnected for timely and safe transactions. The conceptual framework proposed which provides a solution to the problems linked to crowdfunding through the use of blockchain.